Graphene-functionalized photonic crystal fibers for detecting the refractive index of a wide range of analyzes - Salim Neamah, Farah; A Yasser, Hassan (Edelweiss Applied Science and Technology, 2024)
This study looks into a new photonic crystal fiber (PCF) sensor covered in graphene that can detect changes in the analyte’s refractive index (RI) in the COMSOL environment. The sensor operates by detecting a peak in light loss that varies in wavelength based on the RI of the analyte. Higher RI analytes shift the peak towards longer wavelengths. It is explored how many factors affect the sensor’s performance, such as graphene’s Fermi energy, the site inside the fiber, and the thickness of the gold layer. The location of graphene and its Fermi energy have a substantial influence on how the sensor responds. Interestingly, the resonant wavelength has a linear relationship with the RI of the analyte, which allows for precise RI calculation. Increasing gold thickness improves light-material interaction, but subsequent thickening has a detrimental impact, lowering sensor sensitivity. The appropriate thickness varies according to the material under consideration. Finally, the analysis determines the optimal arrangement of graphene for maximum sensitivity by completely covering the analyte holes in the PCF. By finding the right balance between these factors, the suggested sensor can have both high spectral sensitivity and low sensor resolution.